The Indians the Old West - Capps, Benjamin (New York Time-Life Books, 1973)
Illustrated chronicles of Indian life, culture, rituals, confrontations with the white man, etc. on the Western frontier.
Keywords: Indians of North America -- West (U.S.) Indians of North America. West United States